2004
DOI: 10.1097/01.tp.0000128334.93343.b3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of Distribution of Human Bone Marrow-Derived Mesenchymal Stem Cells After Transplantation into Adult Unconditioned Mice

Abstract: These results suggest that human MSC transplantation into unconditioned recipients represents an option for providing cellular therapy and avoids the complications associated with drugs or radiation conditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 26 publications
(41 reference statements)
11
97
1
3
Order By: Relevance
“…The relationship between expression of telomerase and telomere length stabilization and the extension of the life span of the human cell have been reported. 21,22 MSCs, or marrow stromal cells, are multipotential cells. 2,23 Stromal cells of the marrow microenvironment and their associated biosynthetic products provide the physical framework within which hematopoiesis occurs, synthesize or present growth-stimulatory and growthinhibitory factors, produce numerous extracellular matrix ligands, and express a broad repertoire of adhesion molecules that serve to mediate hematopoietic stem cell homing and to transmit regulatory signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between expression of telomerase and telomere length stabilization and the extension of the life span of the human cell have been reported. 21,22 MSCs, or marrow stromal cells, are multipotential cells. 2,23 Stromal cells of the marrow microenvironment and their associated biosynthetic products provide the physical framework within which hematopoiesis occurs, synthesize or present growth-stimulatory and growthinhibitory factors, produce numerous extracellular matrix ligands, and express a broad repertoire of adhesion molecules that serve to mediate hematopoietic stem cell homing and to transmit regulatory signals.…”
Section: Discussionmentioning
confidence: 99%
“…Although Conget showed that human MSC can be detected in mouse bone marrow for as long as 1 year after human MSC infusion, we did the 6-month safety test according to the requirement of the authorities for the new medical product. 21 …”
Section: Safety Profile Of Transplanted Htrt þ Mscsmentioning
confidence: 99%
“…As a result, minimally invasive treatments such as injecting growth factors to stimulate the NP cells to synthesize proteoglycans [74] or injecting cells able to synthesize appropriate ECM such as bone marrow mesenchymal stem cells [48,67,108] are the most commonly proposed. Nevertheless, one important inadequacy of this approach is that the high disc pressure and the aqueous nature of the cell suspension usually result in depletion of the local availability of cells [5,53]. As a result, use of injectable carriers is necessary to effectively deliver cells into the degenerative NP space.…”
Section: Scaffolding In Intervertebral Disc Tissue Engineeringmentioning
confidence: 99%
“…Our data are in good agreement with previously published reports demonstrating that after syngeneic or xenogeneic transplantation of MSCs derived from the bone morrow of mouse, rat or nonhuman primates, donor cells engraft into many tissues of conditioned recipients. [53][54][55][56][57] It is still unclear whether transplanted cells continue to retain their multilineage potentials and clonogenic ability or if they were able to commit into residing tissue. At present, Overall, our results provide evidence supporting the suitability of genetically corrected MSCs by ODN in cellbased therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%